Social status and plasma progesterone profiles of female long-tailed macaques - Kavanagh, Michael; Tan, H. S.; Thambyrajah, V. (Malaysian Society of Applied Biology, 1981)
Over a period of approximately six months, dominance data, copulation frequencies and plasma progesterone levels were recorded for eight female Macaca fascicularis living in a mixed group. The study, which was of a preliminary nature, sought to compare aspects of the reproductive physiology and behaviour of socially dominant versus subordinate animals. The results were not conclusive but they indicated that subordinate females copulate at least as much as dominants. For three subjects, increased ovarian activity seemed to be associated with a rise in social status, suggesting that differences in the reproductive physiology of dominant versus subordinate females would bear further investigation with a larger sample.